Synchronous colon and appendix tumor. A case report - Chancafe-Rodríguez, José Gerardo (2021)
Introduction: Synchronous tumors are extremely rare, the coexistence of colon and appendix cancer is a relatively unusual phenomenon, which poses diagnostic problems when it comes to discriminating the primary or metastatic nature of each of them. This fact occurs in most cases with synchronous mucosecretory adenocarcinomas. Case report: We present the case of a 72-year-old female patient who was admitted to the emergency service of the Las Mercedes Regional Teaching Hospital in Chiclayo due to symptoms of acute abdominal pain, where imaging studies were performed with a presumptive diagnosis of malignant neoplasia of the rectum. operations room. The pathological result shows a diagnosis of tubular adenocarcinoma with a mucinous component in the rectus-sigmoid of a low grade of malignancy (moderately differentiated), with invasion to the adjacent peri-rectal adipose tissue, infiltrative invasion borders and perineural invasion, with a free resection margin and lymph nodes. lymphatics free of malignant neoplasm; In addition to moderately differentiated mucinous adenocarcinoma of the appendix (G2), of diffuse location, the neoplasm invades even the muscularis propria, resection margin free of malignant neoplasia. Conclusion: The importance of this category is that the frequency of malignant neoplasms at the appendicular level is not high, and their simultaneous association with colorectal adenocarcinoma makes them even more unusual